Optimization of Tourism Real Estate Development Project Based on Option Premium Model - Donglei Ying (Discrete Dynamics in Nature and Society)
Compared with that of traditional housing real estate, the development of tourism real estate is time-consuming, complex, and irreversible. It is hard to guide investment decision-making on tourism real estate with the conventional discount cash flow (DCF) method. This paper aims to demonstrate that the real option method can improve and optimize the investment decision-making on tourism real estate. Through case analysis, the real option model, i.e., the classic American real option model, and binary tree value distribution model were adopted to analyze the factors affecting the real option of tourism real estate, optimize the development sequence of tourism real estate project, and demonstrate the phased development value of tourism real state, thereby enhancing the development value of tourism real estate projects. The case analysis proves that tourism real estate investment is fully consistent with real option in the uncertain spatiotemporal attributes: uncertainty, irreversibility, and timeliness. Therefore, tourism real estate project carries obvious features of real option. The decision-making by the real option model is much more scientific and superior than that by the conventional DCF method. Since the application of real option theory has been emphasizing housing real estate over tourism real estate, the research results enrich the theory on real option-based investment decision-making for real estate and expand the application scope of real option.